Beasts before us : the untold story of mammal origins and evolution - Panciroli, Elsa (Bloomsbury Sigma, 2021)
"For most of us, the story of mammal evolution starts after the asteroid impact that killed the dinosaurs, but over the last 20 years scientists have uncovered new fossils and used new technologies that have upended this story. In Beasts Before Us, palaeontologist Elsa Panciroli charts the emergence of the mammal lineage, Synapsida, beginning at their murky split from the reptiles in the Carboniferous period, over three-hundred million years ago. They made the world theirs long before the rise of dinosaurs. Travelling forward into the Permian and then Triassic periods, we learn how our ancient mammal ancestors evolved from large hairy beasts with accelerating metabolisms to exploit miniaturisation, which was key to unlocking the traits that define mammals as we now know them"--provided by publisher.